(untitled) (Journal of Engineering, 2014)
Water injection equipments such as pipelines, which are used in the second recovery of oil in the Al-Ahdeb wells, suffer from the corrosion in water during maintaining vacuum deoxygenated tower that used to decrease concentration of the dissolved oxygen gas in the water from 6.2-9.1 ppm to o.5 ppm. This study involved calculation the corrosion rates of the internal surfaces of the pipelines either during operation of the vacuum unit or when the tower out of operation. Finally, find the solution by one of the following suggestions. In the first suggestion removal of the dissolved O2 from water is achieved by increasing the dosage of the oxygen scavenger (sodium sulphite). The second suggestion involves removing the dissolved O2 from water by bubbling the oxygenated water with nitrogen gas. The study showed that the corrosion rates of various inside diameter pipelines are between 0.13 mm/yr and 1.5 mm/yr during operation of the vacuum tower and between 3.2 mm/yr and 18.5 mm/yr when the tower out of the operation. While the results showed that the corrosion rate of the pipelines when the tower out of operation reached to the acceptable value of 0.1 mm/y when the dissolved oxygen in the injected water removed by increasing the dosage of the sodium sulphite (Na2SO3) to 48-72 ppm. The results also explained that corrosion rates of the pipelines reached to 0.5 mm/y when the dissolved oxygen removed by bubbling the water with nitrogen gas.